Proces przystosowania materiałów dydaktycznych z języka polskiego jako obcego do zasad podejścia zadaniowego - Janowska, Iwona (Postscriptum Polonistyczne, 2020)
Reading CEFR texts that use the taskbased approach to teaching/learning foreign languages enables teachers to develop a critical approach towards the teaching aids that they have at their disposal and the ways they can be used in didactic process. In order to be uptodate and teach Polish as a foreign language according to the rules of taskbased approach the teacher must prepare the teaching aids on his own. However, older textbooks must not necessarily be banned and rejected. They often contain interesting examples of exercises that can be used during language classes. The main topic of the article is to present several ways of adapting the traditional textbooks to teaching and learning through the taskbased approach. The author of the article asserts that it is not the type of textbook that decides about the method of teaching; on the contrary, with a little effort the teacher can apply a taskbased approach using ‘traditional’ materials.